Re-envisioning reading comprehension for english language learners a critical point of view (2013)
When teaching a second language, it is important to bear in mind that the four skills: speaking, writing, listening, and reading must be facilitated and developed with the same relevance. However, some learners might tell their teacher they can understand everything he says, but they are unable to produce; or that they can understand a simple text, but when they face comprehension questions that require a critical level of understanding, they do not perform as expected. It is well known that productive skills depend on receptive skills (listening and reading) due to these serve as models for written and oral production; even though one of the most common problems teachers face with students and one of the most complex processes during teaching is oral and written comprehension, we could say that learners are more exposed to listening than to reading practice.